EXPRESSION TROPHOBLAST CELL B-CELL LYMPHOMA (BCL2) IN EARLY AND LATE-ONSET PREECLAMPSIA - Herman Sumawan; Irwan Taufiqqurachman; Diah Rumekti Hadiati; Dewajani Purnomosari (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
Background: Anti-apoptotic Bcl-2 has an important role that is involved in the regulation of apoptosis. Abnormal apoptotic activity in preeclampsia is caused by the dysregulation of these proteins. Trophoblast antiapoptotic and proapoptotic imbalance is thought to have different influences on the process of early-onset preeclampsia and late-onset preeclampsia Objective: to analyze the difference in Bcl-2 expression in early and late-onset preeclampsia. Method of study: This method was conducted using a cross-sectional study in early-onset preeclampsia compared to late-onset preeclampsia in RSUP. DR. Sardjito Yogyakarta was conducted from April 2019 to June 2019 with consecutive sampling methods. Placental tissue samples were obtained from 26 pregnancies with early-onset preeclampsia and 33 pregnancies with late-onset preeclampsia. The placental expression of Bcl-2 has been investigated by immunohistochemical staining and used semi-quantitative HSCORE examination. Results: The T-test study showed there was a significant difference in Bcl-2 expression among early onset preeclampsia (2.31±0.66 ) and late-onset preeclampsia (2.61±0.43) with p-value 0.047 (p<0.05). Bcl-2 the expression appears lower in early-onset preeclampsia with a mean value of 0.30 (CI 0.04 – 0.60). Conclusion: Thus we can conclude the expression of Bcl-2 is considered lower in early-onset preeclampsia compared to late-onset preeclampsia